Theoretical estimation of the environmental impact of biofuel mixtures - Török, Ádám (Transport, 2009)
Vehicles are burning fuels inefficiently. Nowadays, there is a strong correlation between CO2 emission and climate change. The article estimates a theoretical environmental impact of biofuel mixtures on the transport sector. A high ratio of road transportation in CO2 emission caused by humanity made necessary to research the estimation of the environmental impact of biofuel mixtures. We have to clarify the emission of the transport sector in order to get information about the role of the impact that is a further step to a sustainable society. Sustainable development is a kind of development where the pace of technical development, the satiation of increasing supply and the raw materials and resources of the Earth are poised so that the rate of living and the opportunities of the future generations should not decline. One of the major goals of transport policy of the European Union is sustainable mobility. For this reason, transportation systems must be developed and standardized and the effectiveness of transportation service must be increased while environmental pollution must be decreased or prevented. There is a justifiable demand put forward by the society to moderate the environmental impacts caused by road transportation. This article deals with modelling the environmental impact of ethanol‐gasoline mixtures and diesel oil‐ethanol‐biodiesel mixtures.First published online: 27 Oct 2010